THE USE OF ICT IN ELT: CHALLENGES AND SOLUTIONS (A STUDY OF SD NU CEPOGO 01) - Purnaningtyas, Anis Istirokhah Ayu; Malihah, Noor Malihah (Universitas Wahid Hasyim Semarang, 2024)
In order to ease the students understanding and improve the innovation in teaching, teachers are trying to find best way in delivering material. One of the way is by maximizing the use of Information and Communication Technology (ICT). There are many challenges faced by teachers from many factors such as internet connection, device availability and compatibility and so on and teachers also have solutions as the temporary solutions. This research used qualitative method by selecting the respondent by demography, age, and graduation time. Spreading questionnaires and interviews also observation to the ICT use in the class. The validation of the data is using triangulation method where we compare 3 methods of collecting data and summarize the result. The author recommends that teachers make the challenges the opportunity for self-development. The schools are also recommended for having better and enough ICT tools as their facility.